COVID-19 and bilingual children’s home language environment: Digital media, socioeconomic status, and language status - Sun, He; Tan, Justina; Chen, Wenli (Frontiers in Psychology, 2023)
Input is considered crucial in bilingual children’s language development. This is especially true for bilingual children’s mother tongue language learning given its common reduction in input opportunities due to the dominance of one language within society, as seen in countries and regions from Wales to Singapore. Previous studies tend to focus on the quantity and quality of conventional active communication and resources (e.g., speaking and reading with parents) on bilingual children’s language development, and substantially, fewer studies have explored this topic from the perspective of digital media. However, the COVID-19 pandemic has accentuated the critical role of digital media in various aspects of life, including bilingual children’s home language environment. Thus, to holistically understand bilingual children’s daily language input patterns, it is imperative to explore both their conventional and digital media input resources. The current study focuses on English-Mandarin bilingual children in Singapore and would like to explore (1) whether their conventional and digital media language environments have been affected by the COVID-19 pandemic and (2) whether the societal status of a language and familial socioeconomic status (SES) would affect bilingual children’s conventional and digital media input. Survey data from 162 parents of English-Mandarin bilingual preschoolers (3 to 6 years old) were used to explore the two research questions. Two online parental questionnaires were employed for data collection. One-way repeated-measures MANOVA and path models were used to address the questions. The results indicated that input patterns from nuclear family members had not been affected by COVID-19; however, the amount and frequency of conventional and digital media materials and activities increased significantly since COVID-19. Higher-SES families possessed more conventional materials and conducted conventional activities more often, while lower-SES families possessed more digital media materials. Both conventional and digital media materials and activities were richer in English than in Mandarin. Higher-SES families perceived digital media usage for learning to be of less importance than lower-SES families. The implications for early bilingual learning following COVID-19 are discussed.